Optimasi Unjuk Kerja Pendinginan Konveksi Paksa pada Jet Sintetik Berbasis Speaker dengan Variasi Nozzle Berbentuk Abjad X dan Z - Salma Zafirah Wisriansyah (2020)
Synthetic jet is considered as a promising solution to be used as a cooling device in a modern electronic that requires a slim body. There are several variables that can be used in synthetic jet studies such as nozzle shapes and frequency excitations. This study chose to vary the shape of the nozzle by using X and Z alphabet shape. Other than as an innovation, this study wanted to prove that the existence of corners in X and Z shape could actually increase the heat transfer if compared to the conventional nozzle shape (circle). This study is done by using speaker as an actuator with sinusoidal wave. The result of this study experimentally showed that X and Z shaped nozzle could produce the best final temperature of the heat source at 40 Hz, 60 Hz and 80 Hz. Moreover, the computational result of this study found that the highest vorticity magnitude occurred is produced by Z shaped nozzle in all frequency excitations whilst the highest velocity magnitude is generated by X shaped nozzle in all frequency excitations as well. This study showed that the X and Z shaped nozzle could increase the heat transfer compared to the circle shaped one.